China and South Africa in the context of South-South cooperation: cooperation in the United Nations and World Trade Organisation - Matshanda, Namhla Thando (My University, 2010)
ABSTRACT South-South cooperation has become one of the most powerful tools at the disposal of developing countries for integration into the global economy. South-South relations that gained momentum in the aftermath of the Cold War have demonstrated a radical departure from the now archaic modes of engagement characteristic of the Cold War era. A handful of developing countries have emerged as de facto leaders of the South. These are countries that have taken significant rhetorical as well as practical steps towards strengthening South-South cooperation, as a means to counter the global domination of the affluent states of the North. This research report investigates the Post-Cold war adaptation of South-South cooperation exemplified by China and South Africa, and how they cooperate in international fora, with focus on the United Nations and World Trade Organisation. These are two countries that are strong advocates of South-South solidarity, and are regarded as leading powers of the developing world. Although with varying political and economic formations, the two countries have much in common. The most salient commonality is their evolving foreign policies. It is their evolving foreign policies that have enabled China and South Africa to take particular positions in international forums. There is significant commitment to the South agenda and this is demonstrated in UN and WTO engagements. However, there is ample room for improvement. Though committed to South-South cooperation, China and South Africa are still more committed to national interests. For South-South cooperation to move beyond rhetoric and periodic instances of cooperation there is an urgent need to redefine South-South cooperation. A new definition should involve a significant shift from the current abstract characterisation, to one that focuses on specific issues whose progress can be monitored and measured.
Keywords: South-South cooperation; China; South Africa; United Nations; World Trade